Slide Rule (1961)
Slide rules were common tools for engineering students at Cal Poly. On February 17, 1961, El Mustang announced a lecture by John Gascoyne of C. F. Braun Corporation on programming the Bendix G-150 computer, which would "impress upon the engineering students the fact that to be able to program a digital high speed computer is a requirement for getting ahead in the engineering world...slide rules, desk calculators and adding machines are no longer the tools of the trade."